First Annual Report of the Improvement of the Central Park, New York (January 1, 1857) Appendix A, 106 (Chas. W. Baker 1857) - (:unkn) unknown (My University, 1857)
Among other activities, restricts carry of firearms and throwing of stones or other missiles in Central Park.
Keywords: CARRY - CERTAIN PUBLIC PLACES